Does Phobos Reflect Solar Wind Protons? Mars Express Special Flyby Operations With and Without the Presence of Phobos. Issue 11 (18th November 2021) - Futaana, Yoshifumi; Holmström, Mats; Fedorov, Andrey; Barabash, Stas
Abstract: We characterize the solar wind proton reflection (backscattering) from Phobos using a series of Mars Express operations. The plasma data obtained during the Phobos flyby of Mars Express in January 2016 showed a non‐solar wind signal possibly reflected from the Phobos surface. Similar signatures were previously reported during an earlier Phobos flyby in 2008. On the other hand, although Mars Express has encountered Phobos (within 100 km) more than 10 times, it has thus far detected only two clear cases of reflected protons. The intermittency of the reflected proton detections could indicate that these protons are not from Phobos but are produced by the spacecraft body or solar arrays under a special attitude configuration during the flyby maneuver. To rule out these artifacts as the cause, we conducted three special operations; Mars Express was operated using the identical attitude and solar panel control sequence but without Phobos nearby. All the measured plasma data during the special operations exhibit no additional plasma signatures. These fake flyby experiments indicate that the measured non‐solar wind protons during the real flyby are not from the spacecraft and that Phobos likely reflects solar wind into space. On the other hand, the intermittency of the reflected protons from Phobos remains unexplained. The reflected protons are vital additional plasma components because they inject enough energy to disturb the near‐Phobos plasma environment. In addition, we can utilize these reflected particles to remotely measure the surface precipitation flux. Plain Language Summary: How does a Martian moon, Phobos, interact with solar wind plasma? Because Phobos lacks an atmosphere and a magnetic field, solar wind plasma directly impacts the surface. The fate of solar wind protons must resemble that of Moon‐solar wind interactions. The solar wind protons are reflected back from the lunar surface. Phobos must similarly reflect solar wind protons; however, only two flybys out of dozens of Mars Express flybys have shown such proton reflection. Here, we show the second event in which these ions were detected using a new instrument operation mode. Moreover, to rule out the possibility that the spacecraft body produced such protons, we ran three more "flyby" operations strictly following the attitude control sequence but without Phobos nearby. These "fake flybys" without Phobos prove that the proton signatures measured during the previous actual flybys were not instrument effects produced by the spacecraft body. The reflected proton signatures are different between Phobos and the Moon. Why they are different remains an open question, but the behavior of plasma at the surfaces of these bodies may differ. Because solar wind plasma modifies rocky surfaces in space, the different interactions imply evolution differences between the Moon and Phobos surfaces. Key Points: Mars Express identified non‐solar wind protons near Phobos during a flyby, possibly from the surface of Phobos The protons showed abrupt changes with a time scale of 30 s or a spatial scale of ∼70 km Special maneuvers of Mars Express rule out possible instrument effects during the Phobos flyby